THE INFLUENCE OF SOCIO-ECONOMIC A ND MANAGERIAL FACTORS OF FARMERS ON THE SUCCESS OF AGROFORESTRY MODEL FARMING AGRISILVICULTURE PATTERN - Wibawa, Ismail Supriyatna; Dasipah, Euis; Mulyana, Tatang (Universitas Majalengka, 2024)
This study aims to Influence Farmers' Socio-Economic and Managerial Factors on the Success of Farming with Agroforestry Models with Agrisilvicultural Patterns. (A Case of Farmers around the Kiarapayung Regional Forest. The respondent determination technique was carried out by census as many as 65 respondents. The analysis technique used was path analysis. The results obtained were the performance of the socio-economic factors of farmers who were active in the agroforestry model of agrisilvicultural patterns in the forests of the Kiarapayung area which included: age; education; experience; family dependents; land area; and capital obtained 48.78% achievement criteria Enough. This illustrates the socio-economic factors of farmers seen from age are old age (54 years); low education mostly elementary school graduates; family dependents of 2 people, narrow land 0.26 ha, and low capital Managerial performance of agroforestry farmers in agricultural patterns around the Kiarapayung forest area obtained an achievement level of 73.07% good criteria Consisting of technical managerial achievements obtained 83.37% very good criteria and business managerial 65.49% good criteria. Successful performance of an agroforestry model farming agrisilvicultural pattern of farmers around the forest area of Kiarapayung which consists of Social Aspects 66.54% Good criteria; Economic Aspect 63.46% Good Criteria and Ecological Aspect 64.42% Good Criteria. The overall level of achievement obtained 64.91% criteria Good. There is a real and strong positive correlation between socio-economic factors and managerial agroforestry farmers with agrisilvicultural patterns, which is indicated by the correlation coefficient r = 0.365, it can be interpreted that the better the socio-economic factors, the better the managerial farmers. The hypothesis is proven that the socio-economic and managerial factors of farmers have a positive effect on the success of the agroforestry model of the agrisilvicultural pattern, either simultaneously or partially. The total influence of the two variables is 67.00% which is contributed by the total influence of socio-economic factors 9.32% and the total managerial influence of farmers is 57.69%, the remaining 37.00% is influenced by other factors. Efforts need to be made to increase the productivity of the types of seasonal crops cultivated by increasing the amount of use of organic fertilizers, and coaching for follow-up and control so that farmers remain interested and continue to apply the agroforestry farming model.